Follow-Up at 2 years After Emergency Surgery for Constrictive Pericarditis Complicated With Gastrointestinal Bleeding - Xu Zhao MM; Chuntian Li MM; Yue Zhong MM; Xin Mao MM; Guiqing Liu MD; Feng Wang MD; Guiyou Liang MD (Inquiry: The Journal of Health Care Organization, Provision, and Financing, 2022)
Chronic constrictive pericarditis (CCP) is one of the common causes of cardiogenic cirrhosis; it is rare for a patient to have both CCP and recurrent black stool, so we consider that CCP causes cardiogenic cirrhosis. Cardiogenic cirrhosis caused portal hypertension which then resulted in gastrointestinal bleeding. Herein, we report a case of a 40-year-old Chinese woman suffering from CCP who had upper gastrointestinal bleed and had to undergo emergency surgery. Two years after the emergency surgery, multiple reexaminations showed significantly improved cardiac functions, hemoglobin, and WBC levels and gastrointestinal functions.